Health Insurance and Out-of-Pocket Costs in the Last Year of Life among Decedents utilizing the ICU - Khandelwal, Nita (Crit Care Med, 2019)
OBJECTIVE: Use of intensive care is increasing in the U.S. and may be associated with high financial burden on patients and their families near the end of life. Our objective was to estimate out-of-pocket (OOP) costs in the last year of life for individuals who required intensive care in the months prior to death and examine how these costs vary by insurance coverage. DESIGN: Observational cohort study using seven waves of post-death interview data (2002-2014) from the Health and Retirement Study. PARTICIPANTS: Decedents (n=2,909) who spent time in the ICU at some point between their last interview and death. MEASUREMENTS AND MAIN RESULTS: Two-part models were used to estimate OOP costs for direct medical care and health-related services by type of care and insurance coverage. Decedents with only traditional Medicare fee-for-service (FFS) coverage have the highest OOP spending in the last year of life, estimated at $12,668 (95% CI: $9,744-15,592), second to only the uninsured. Medicare Advantage and private insurance provide slightly more comprehensive coverage. Individuals who spend-down to Medicaid coverage have 4x the OOP spending as those continuously on Medicaid. CONCLUSIONS: Across all categories of insurance coverage, OOP spending in the last 12 months of life is high and represents a significant portion of assets for many patients requiring intensive care and their families. Medicare FFS alone does not insulate individuals from the financial burden of high intensity care, due to lack of an OOP maximum and a relatively high co-payment for hospitalizations. Medicaid plays an important role in the social safety net, providing the most complete hospital coverage of all the insurance groups, as well as significantly financing long-term care.